Essential birds - Ringstad, Arnold (2022)
Examines Earth's birds, highlighting a diverse selection of 22 notable species from around the world. A blend of narrative text, authoritative nonfiction content, fact boxes, and vivid photos bring these amazing birds to life. Features include a glossary, online resources, source notes, and an index.
Includes bibliographical references (page 106) and index.
Agees 9-13
Keywords: Birds -- Juvenile literature; Birds -- Behavior -- Juvenile literature; Animals -- Identification -- Juvenile literature; Zoology -- Juvenile literature